2018
DOI: 10.1590/0103-8478cr20180433
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-agronomic characterization and analysis of genetic divergenceamong accessions of tomatoes (Solanum lycopersicum L.)

Abstract: The collection and characterization of tomato germplasm are of relevant importance for agriculture. This study aimed to collect and characterize, by way of morphological description and statistical tools for the composition of groups, tomato accesses from the Southern and Serrana regions of the State of Espírito Santo, as well as to establish the tomato germplasm bank of the Ifes - Campus de Alegre. Thirty-seven accessions were collected from different commercial locations of Espírito Santo. The experiment was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
4
0
2
Order By: Relevance
“…Similarly to our results, Rocha et al (2010) [37] observed the red colour of the fruit in 25 of the 40 varieties of cherry tomatoes (62.5%) grown organically. Other studies showed the same predominance of red [38][39][40]. In addition to the various shades of red of the fruit, the above authors identified other colours, but in proportions: pink, yellow, orange, and green, as well as all of their different combinations.…”
Section: Characteristics Of Tomato Landracesmentioning
confidence: 56%
See 1 more Smart Citation
“…Similarly to our results, Rocha et al (2010) [37] observed the red colour of the fruit in 25 of the 40 varieties of cherry tomatoes (62.5%) grown organically. Other studies showed the same predominance of red [38][39][40]. In addition to the various shades of red of the fruit, the above authors identified other colours, but in proportions: pink, yellow, orange, and green, as well as all of their different combinations.…”
Section: Characteristics Of Tomato Landracesmentioning
confidence: 56%
“…The main groups for classifying the shape of the fruit in tomatoes differed according to the author: round, slightly flattened, cylindrical, and round elongated [40]; globular, cordiform, cylindrical, pear-shaped, and slightly flattened [39]; slightly flattened, flattened and round [38]. However, in all the studies mentioned above, round and round-flattened shapes were predominant.…”
Section: Characteristics Of Tomato Landracesmentioning
confidence: 99%
“…Esse resultado indica que os frutos dos 5 híbridos variam entre tons de amarelo, alaranjado e vermelho, demonstrando uma distinção entre os outros dois grupos. A cor do tomate é um indicativo de substâncias denominadas carotenoides, estas substâncias dão a coloração amarela, laranja e vermelha, sendo os tipos mais relatados na composição do tomate, o licopeno e o β-caroteno (FERNANDES et al 2018), associado a acentuada síntese de licopeno (CARVALHO et al, 2005;LÓPEZ-CAMELO et al, 2004).…”
Section: Parâmetros Qualitativos Dos Frutosunclassified
“…A demanda dos tomates do grupo Saladete também conhecidos como italiano tem aumentado no Brasil, além de apresentar alto teor de sólidos solúveis totais, os frutos são indicados tanto para processamento, quanto para consumo in natura (FERNANDES et al, 2018), proporciona frutos alongados, biloculares, polpa espessa e são firmes e saborosos.…”
Section: Introductionunclassified
“…Qualitative and quantitative characteristics determine the agronomic value and taxonomic classification of plants. Variations in these characteristics are critical for varietal identification and selection, and breeders need suitable knowledge of tomato genetic diversity to identify and improve tomato genotypes with desirable characteristics in terms of agricultural traits, disease resistance, harvest yield and quality (Fernandes et al 2018, Rosenqvist et al 2019. Moreover, the development of phenotypic-genetic markers that are closely linked to EB disease resistance facilitates the introgression of phenotypic traits into marker-assisted selection in resistance breeding and identification of resistant tomato genotypes (Mongiano et al 2020, Nafisa et al 2020.…”
Section: Introductionmentioning
confidence: 99%